2017
DOI: 10.1002/ijc.30705
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U alters bioenergetics and expands the cancer stem cell phenotype in HER2‐positive breast cancer

Abstract: Neuromedin U (NmU) is a neuropeptide belonging to the neuromedin family. Recently, we reported a significant association between NmU and breast cancer, particularly correlating with increased aggressiveness, resistance to HER2-targeted therapies and overall significantly poorer outcome for patients, although the mechanism through which it exerts this effect remained unexplained. Investigating this, here we found that ectopic over-expression of NmU in HER2-positive breast cancer cells induced aberrant metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Studies have shown that overexpression of NMU is associated with tumorigenesis and development of various malignancies [12][13][14][15][16][17][18][19]. However, to date no studies have examined the association of NMU and HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that overexpression of NMU is associated with tumorigenesis and development of various malignancies [12][13][14][15][16][17][18][19]. However, to date no studies have examined the association of NMU and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropeptide has been demonstrated to be associated with a range of different physiological functions, including smooth muscle contraction, energy homeostasis, nociception, circadian control, bone remodeling, and immune regulation [9][10][11]. A limited number of studies had suggested that NMU may play an oncogenic role in the progression of various cancers, including lung cancer, pancreatic cancer, breast cancer, renal cancer, and endometrioid endometrial carcinoma, through promoting migration, invasion, glycolysis, a mesenchymal phenotype, a stem cell phenotype of cancer cells, and resistance to the anti-tumor immune response [12][13][14][15][16][17][18][19]. However, besides a report of NMU exacerbating non-alcoholic steatohepatitis (NASH) [20], the effects of NMU on liver diseases, especially on HCC, have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…NPY was reported to promote inflammation-induced tumorigenesis via PI3-K/Akt pathway and miR-375-dependent apoptosis ( Jeppsson, Srinivasan & Chandrasekharan, 2016 ). NMU was associated with increased breast cancer aggression ( Martinez et al, 2017 ) and its overexpression induced regional metastasis of head and neck squamous cell carcinoma ( Wang et al, 2016 ). KNG1 was identified as a potential marker of early colorectal cancer stages ( Quesadacalvo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work had shown an association between overexpression of NmU and an expansion of cells with CSC phenotype. 32 The CSC phenotype is characterized by increased drug resistance and also by enhanced immune evasion. 33-35 In accordance with this, as well as driving HER2-targeted drug resistance, NmU overexpression was also associated with increased expression of TGFβ 1 and PD-L1, known inhibitors of the immune response.…”
Section: Discussionmentioning
confidence: 99%